Phenotypic and Genotypic Investigation of Two Representative Strains of Microbacterium Species Isolated From Micro-Filtered Milk: Growth Capacity and Spoilage-Potential Assessment - Bellassi, Paolo; Cappa, Fabrizio; Fontana, Alessandra; Morelli, Lorenzo (Frontiers in Microbiology, 2020)
The microbiota that spoils long-life micro-filtered milk generally includes species of the genus Microbacterium. The metabolic properties of this group of microorganisms that could potentially modify the quality of micro-filtered milk are still unexplored when compared to better-known microorganisms, such as the spore-forming Bacillus and Paenibacillus spp., and Gram-negative contaminants, such as species of the genera Pseudomonas and Acinetobacter. In this preliminary study, two strains of Microbacterium (M. lacticum 18H and Microbacterium sp. 2C) isolated from micro-filtered milk were characterized in depth, both phenotypically and genotypically, to better understand their role in long-term milk spoilage. The study highlights the ability of these strains to produce high cell numbers and low acidification in micro-filtered milk under storage and shelf-life conditions. Phenotypic analyses of the two Microbacterium sp. isolates revealed that both strains have low proteolytic and lipolytic activity. In addition, they have the ability to form biofilms. This study aims to be a preliminary investigation of milk-adapted strains of the Microbacterium genus, which are able to grow to high cellular levels and perform slight but not negligible acidification that could pose a potential risk to the final quality of micro-filtered milk. Furthermore, M. lacticum 18H and Microbacterium sp. 2C were genotypically characterized in relation to the characteristics of interest in the milk environment. Some protein-encoding genes involved in lactose metabolism were found in the genomes, such as β-galactosidase, lactose permease, and L-lactate dehydrogenase. The phenotypically verified proteolytic ability was supported in the genomes by several genes that encode for proteases, peptidases, and peptide transferases.